(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The postoperative period is accompanied by a high risk of thrombotic and hemorrhagic complications, which requires timely monitoring of the hemostasis system. A modern and informative method for assessing coagulation status is thrombodynamics, a laboratory test that allows real time visualization and quantification of the thrombosis process. This article discusses the advantages of using thrombodynamics in the postoperative period for early detection of hypercoagulation and individualization of anticoagulant therapy. The data on the diagnostic and prognostic significance of the method in patients after surgical interventions of various profiles are presented. The importance of integrating thrombodynamics into the management protocols of postoperative patients in order to reduce the risk of thrombosis and improve clinical outcomes is noted.